STUDY OF MARINE ECOTOURISM POTENTIAL IN TURELOTO BEACH REGENCY NORTH NIAS NORTH SUMATERA PROVINCE - Angelia E Bernike Zebua; Dessy Yoswaty; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Ecotourism is a tourist trip to a natural region in order to conserve or save the environment and provide welfare to the local population. This research was conducted in February-March 2017 at Tureloto beach, North Nias, North Sumatera Province. The study aims to determine the potential of marine ecotourism and aspects of the strength of Tureloto beach to be developed as a marine ecotourism area. The method used in this research is survey method and station point determination by purposive sampling. Mainland coastal Tureloto is the result of removal of the seabed one to three meters above sea level due to the earthquake that occurred in 2005. Value of Travel Assessment Index that is on Station I, II, III and IV is 79.5%, 89.1%, 76.3% and 64.1% respectively. Assessment of strengths, weaknesses, opportunities, and threats, the development of Tureloto's coastal potential is assessed from observations at research sites, interviews and questionnaires. Tureloto Beach has the potential as a marine ecotourism area such as pristine, natural and exotic natural beauty, marine biota and various coral reefs, history of coastal geology, waters conservation zonation system as well as research resources. Aspects of Tureloto's coastal strengths are, empowerment of local communities and on the coastal can be added a place to relax.Keyword: Potential, Marine Ecotourism, Tureloto Beach